2012
DOI: 10.1155/2012/375673
|View full text |Cite
|
Sign up to set email alerts
|

Fagopyrum tataricum(Buckwheat) Improved High-Glucose-Induced Insulin Resistance in Mouse Hepatocytes and Diabetes in Fructose-Rich Diet-Induced Mice

Abstract: Fagopyrum tataricum (buckwheat) is used for the treatment of type 2 diabetes mellitus in Taiwan. This study was to evaluate the antihyperglycemic and anti-insulin resistance effects of 75% ethanol extracts of buckwheat (EEB) in FL83B hepatocytes by high-glucose (33 mM) induction and in C57BL/6 mice by fructose-rich diet (FRD; 60%) induction. The active compounds of EEB (100 μg/mL; 50 mg/kg bw), quercetin (6 μg/mL; 3 mg/kg bw), and rutin (23 μg/mL; 11.5 mg/kg bw) were also employed to treat FL83B hepatocytes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 37 publications
(45 reference statements)
1
48
0
1
Order By: Relevance
“…Many studies have demonstrated the biological activities of various TB nutrients and phytochemicals, such as protein [7,8], dietary fiber [9], and polyphenols [10]. These nutrients and compounds have been shown to improve hypercholesterolemia, hyperlipidemia, and hyperglycemia in rodent models; however, few studies have examined the health benefits of buckwheat, as a whole food, in humans.…”
mentioning
confidence: 99%
“…Many studies have demonstrated the biological activities of various TB nutrients and phytochemicals, such as protein [7,8], dietary fiber [9], and polyphenols [10]. These nutrients and compounds have been shown to improve hypercholesterolemia, hyperlipidemia, and hyperglycemia in rodent models; however, few studies have examined the health benefits of buckwheat, as a whole food, in humans.…”
mentioning
confidence: 99%
“…The 75% ethanol extracts of buckwheat was abbreviated to be EEB in this study. The quercetin and rutin of EEB were assayed by HPLC, and results suggested that 228.8 mg/g of rutin and 58.6 mg/g of quercetin were present in EEB (Lee, Hsu, Shen, Cheng, & Wu, 2012). …”
Section: Preparation Of Samplementioning
confidence: 99%
“…However, the studies on buckwheat proteins, especially on buckwheat protease inhibitors, have mainly focused on their antitumor activities (Cui et al, 2013;Ferreira et al, 2013;Liu et al, 2001). It has been well known that buckwheat can reduce levels of blood sugar, lower cholesterol, and protect against heart disease (Hosaka et al, 2014;Lee et al, 2012;Stringer et al, 2013), partly due to its high level of protease inhibitors. All these properties of buckwheat protease inhibitors are associated with aging.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we hypothesized that rBTI could elicit its beneficial effects by mimicking CR. Because there are some similar physiology effects between CR and buckwheat, such as low blood glucose, low fat content, anticancer, resistance to oxidative stress (Hosaka et al, 2014;Lee et al, 2012;Speakman and Mitchell, 2011;Stringer et al, 2013), and buckwheat contain rich BTI.…”
Section: Introductionmentioning
confidence: 99%